ETIKA AUDITOR MEMODERASI PENGARUH KOMPETENSI, INDEPENDENSI, DAN PROFESIONALISME TERHADAP KUALITAS AUDIT (Studi Kasus Pada KAP Di Wilayah Jawa Tengah) - Hardian Nurul Agustin, 12.05.52.0173; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2016)
This study aims to examine the Auditor Ethics Moderating Effect of Competence, Independence, and the professionalism of the Audit Quality moderated by auditor ethics. In this study, the population used is the auditor who works in Public Accounting Firm (KAP) located in Java Tengah. Sample selected in this study was conducted using purposive sampling, sampling studies based on specific criteria. The criteria for determining that the sample is the auditor who has audit experience and has worked for more than two years. This was felt two years quite auditor respondents have experience auditing the financial statements so that respondents could fill out the questionnaire properly so that the sample in this study amounted to 50 respondents. Based on the results of the study indicate that there are no negative effects and no significant between competence to quality affects the quality of auditors, there are no positive effect and no significant between independence against quality of auditor, there is positive and significant correlation between professionalism to quality of auditor, there is positive and significant between ethics auditor to quality of auditor, there are no positive effect and was not significant between the interaction compensation and ethics audits of quality, there are no positive effect and was not significant between the interaction of independence and ethics audits of quality of auditor, there are no positive effect and no significant between interaction professionalism and ethics audit of the auditor quality.Keywords: Competence, Independence, Professionalism, Ethics Auitor, Quality Auditor